STATE REGULATION BALTO-BLACK SEA PARTNERSHIP IN THE FOREIGN POLICY OF UKRAINE AND POLAND - Kryshtanovych , M. F. (Theory and Practice of Public Administration, 2021)
The article studies the regulation of the Baltic-Black Sea partnership in the foreign policy of Ukraine and Poland. It should be noted that in the conditions of the existence of the USSR, Polish officials did not dare at that time to fully recognize the Ukrainian state and establish full-fledged diplomatic relations with Ukraine. Close contacts between Ukraine and the Republic of Poland took place after December 2, 1991, Poland was the first in the world to recognize Ukraine’s sovereignty. Particularly noteworthy is the fact that on January 4, 1992, diplomatic relations were established between the countries, which contributed to the establishment of regular relations between the countries, because now both have become independent states and full-fledged subjects of international politics. It was found that the idea of creating a union of countries located between the Baltic and Black Seas was first announced in 1919 at a conference held in Latvia and brought together representatives of the governments of Poland, Ukraine, Lithuania, Latvia, Estonia and Finland. Significant contribution to the development of the program for the development of Mizhmopia’s cages in the Foreign Minister of Latvia S. Mejerovits. This program mictila plan for a defense union. At the same time, certain formal steps were taken, in particular - a declaration was signed on the creation of a union on the basis of a confederation, but further, through certain misunderstandings, things did not go. In 1993, at the Conference on Security and Cooperation in Europe, the then President of Ukraine L. Kravchuk raised the issue of creating the necessary space in Central and Eastern Europe for political stability and security at the level of a representative international forum. The formation of the Baltic-Black Sea Federation could become a reality, since even then, the leading Western European countries, naturally, could not ignore the political situation in the East of the continent, proposing their initiatives to resolve it. Nay closer to the implementation of a similar project in the framework of the international spirovrobitstva was such a title of the project of Kacpiysko-Chopnomopsko-Balkobybolt in 2007-2008, during the initiation of current presidents in Ukraine and Poland, V. Yushchenko and L. Kachinsky. Yogo pidtpimaly in the Baltiysky krains, Azerbaijan and Gruziya. Today, the Baltic-Black Sea Union can become a significant obstacle to the implementation by Russia of its revanchist and expansionist concepts. In this context, a special danger for Russia is the friendly relations between the countries that have the prospect of realizing the idea of “Intermarium”, in particular - Lithuania, Poland and Ukraine.